DNA Damage and Repair in Glioblastoma: Emerging Therapeutic Perspectives - I. F. Gareev; O. A. Beylerli; S. A. Roumiantsev (Креативная хирургия и онкология)
Aggressive and therapy-resistant glioblastoma is among the most lethal malignant tumors in humans. Complete surgical resection is often unachievable; therefore, combination chemoradiotherapy is used to target tumor cells residual beyond the resection margin. This approach induces DNA damage in tumor cells and activates the apoptosis pathway. Unfortunately, recurrence remains a major clinical challenge, frequently manifesting as more aggressive and treatmentresistant glioblastoma phenotypes. The DNA repair and damage response (DDR) pathways are critical for maintaining genome stability. While defects in these mechanisms contribute to oncogenesis, they also make tumor cells vulnerable to DNA-damaging therapy, as the cells become dependent on residual repair capacity. It is of paramount importance to understand the molecular components of these mechanisms and to identify potential therapeutic/pharmacological targets for improving outcomes in glioblastoma patients. A subpopulation of stem-like cells, designated as glioblastoma cancer stem cells (CSCs), has been identified as a critical factor in the initiation, maintenance, and recurrence of tumors. These cells exhibit therapy resistance due to enhanced DNA repair capacity. In addition, emerging evidence suggests a link between carbohydrate metabolism and DNA repair pathways, thereby revealing novel therapeutic vulnerabilities in glioblastoma. This review examines current strategies targeting DNA repair mechanisms in glioblastoma. We present a synopsis of recent advancements in research concerning the mechanisms and factors involved in the elimination of DNA damage induced by ionizing radiation and temozolomide (TMZ). Furthermore, we explore the potential of DNA repair pathway inhibitors under investigation in preclinical and clinical trials.